Analisis Faktor-Faktor yang Mempengaruhi Volume Produksi Padi Provinsi Aceh - Nurviana; Ulya Nabilla; Nirmala Sari (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2023)
The agricultural sector has a very significant contribution to the achievement of the Sustainable Development Goals (SDG's) and is also the second largest contributor to Gross Domestic Product (GDP). Aceh's agricultural sector excels in various commodities such as rice, corn, soybeans, and chili. One of the main commodities in Aceh's agricultural sector is rice. Rice is a staple food commodity for the Indonesian people whose needs continue to increase along with the increase in population and also as a source of income for the farming community in meeting their needs. The volume of rice production from year to year fluctuates greatly, experiencing a decrease or increase. the realization of the rice harvest from January to December 2022 amounted to 271.75 thousand hectares, or decreased by around 25.31 thousand hectares (8.52 percent) compared to 2021 which reached 297.06 thousand hectares. The purpose of this study is to analyze the factors that affect the volume of rice production in Aceh Province. The results of the study obtained a regression model Y = 556505,224 + 3,081 X1-1376,14 X2 + 139,57 X3 + 92,797 X4-1,019 X5. The results of the simultaneous test show that the harvest area, rainfall, irrigation area, seed use, and labor together or simultaneously have a significant effect on rice production at a significance level of 0.05. Partially, the variable that has a positive and significant effect on rice production is the variable of harvest area. In addition, the variable area of irrigation and the use of seeds also have a positive effect on rice production but not significant. Meanwhile, the variables of average rainfall and labor have a negative effect on rice paddy production.